Problematyka praw dziecka oraz roli zabawy w procesie jego rozwoju i wychowaniu w świetle poglądów wybranych przedstawicieli myśli pedagogicznej XX wieku - Buława-Halasz, Joanna (Biuletyn Historii Wychowania, 2020)
The twentieth century was special in the history of all mankind. Through many wars, a sense of security was disturbed, basic human needs were not satisfied. Paradoxically, it was at this age that particular attention was paid to children and their needs. This time became the century of the child through the recognition of his rights, which was particularly manifested in the appreciation of the role of play in upbringing.